2023
DOI: 10.1038/s41598-023-35759-4
|View full text |Cite
|
Sign up to set email alerts
|

Three-month outcomes of faricimab loading therapy for wet age-related macular degeneration in Japan

Ryo Mukai,
Keiko Kataoka,
Koji Tanaka
et al.

Abstract: This multicenter study aimed to assess the short-term effectiveness and safety of faricimab in treatment-naïve patients with wet age-related macular degeneration (wAMD) in Japan. We retrospectively reviewed 63 eyes of 61 patients with wAMD, including types 1, 2, and 3 macular neovascularization as well as polypoidal choroidal vasculopathy (PCV). Patients received three consecutive monthly intravitreal injections of faricimab as loading therapy. Over these 3 months, visual acuity improved gradually compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Moreover, a complete regression of polypoidal lesions was observed in 52% of eyes with PCV. Regarding safety profile, two eyes developed retinal pigment epithelium tears, but no other ocular or systemic complications were observed [ 21 ].…”
Section: Neovascular Age-related Macular Degeneration (Namd)mentioning
confidence: 99%
“…Moreover, a complete regression of polypoidal lesions was observed in 52% of eyes with PCV. Regarding safety profile, two eyes developed retinal pigment epithelium tears, but no other ocular or systemic complications were observed [ 21 ].…”
Section: Neovascular Age-related Macular Degeneration (Namd)mentioning
confidence: 99%
“…Notably, by the 48-week mark, approximately 78–80% of patients were allocated a treatment interval of either 12 or 16 weeks 5 . However, real-world clinical settings often employ the treat-and-extend (TAE) regimen 7 as a common treatment strategy. Despite its widespread use, there is currently a dearth of reports on the treatment outcomes of faricimab when utilising TAE regimens over a period of 1 year.…”
Section: Introductionmentioning
confidence: 99%
“…The TENAYA and LUCENE trials showed that the effect of faricimab appears to be prolonged compared with that of aflibercept in terms of maintaining best-corrected visual acuity (BCVA) outcomes 13 . Following the introduction of faricimab, short-term studies reported improved BCVA and retinal morphology during the loading phase of intravitreal faricimab (IVF) treatment in patients with treatment-naïve nAMD 14 , 15 . A few studies have shown efficacy of IVF in nAMD patients who have shown resistance to aflibercept and/or bevacizumab 11 , 16 .…”
Section: Introductionmentioning
confidence: 99%